Bibliometric analysis of the impacts of COVID-19 on the mental health of college students - Tian, Jianxiang; Huilin Yang; Linshu Luo; Libo Dai; Junyu Pan (Journal of the Pakistan Medical Association, 2025)
The current narrative review was planned to summarise research on the effects of coronavirus disease-2019 on the mental health of college students. A total of 1,695 studies from the Web of Science Core Collections database were accessed using VOSviewer software. China and the United States jointly contributed almost half of the overall publications, while the United States and the United Kingdom demonstrated the strongest collaborative network, and the University of Toronto was the research institution with the highest number of publications; 34(2%) papers and 2,330 citations. The current hotspots could be categorised into four areas, with stress, anxiety and depression being the most prominent. Those effects varied based on their academic major, gender, learning status and social support. The findings underscored the immediate need to cultivate international collaboration and interdisciplinary authorship, alongside the implementation of tailored preventive measures. Key Words: Depression, Mental health, Pandemic, COVID-19, Bibliometrics, Anxiety.